The Concept of Hope in The Western and Eastern Perspective - Azizunnisak Hidayati Wahyuna; Susi Fitriana (International Journal of Islamic Educational Psychology, 2020)
Hope is a defining element of effort, social change, awareness, and reason. The object of hope is a life that more complete, a life that more great, deliverance from eternal boredom, or for salvation or for revolution. Hope is paradoxical. Hope is a form of feeling associated with the time dimension. Everyone has different hope in life. However, sometimes we may find people with no hope. Humans who have no hope known as passive-apathetic people, while people who have hope as people who will always make themselves optimistic-active.